Analisis Rasio Keuangan PT. Gruti Lestari Pratama Periode 2019-2023 - Ribka Rehulina; Fatma Dwi Jati; Raya Puspita Sari Hasibuan (AKUNTANSI 45, 2026)
This study aims to analyze the financial performance of PT Gruti Lestari Pratama using liquidity, solvency, profitability, and activity ratios. The data used are secondary data obtained from the company's financial statements, then processed using descriptive analysis techniques. The results of the study indicate that the company is considered quite good in managing current assets and short-term liabilities, as reflected in the liquidity ratios (current ratio, quick ratio, and cash ratio). In addition, the company is also considered capable of managing assets, equity, and liabilities based on the results of the solvency ratios (debt to asset ratio and debt to equity ratio). However, the company's performance in terms of profitability is still less than optimal, as seen from the net profit margin, return on assets, and return on equity. Similarly, the effectiveness of inventory management based on the activity ratio shows less than optimal results.